White lesions in the oral cavity: A clinicopathological study from a tertiary care dermatology centre in Kerala, India - S M Simi; G Nandakumar; T S Anish (Wolters Kluwer Medknow Publications, 2013)
Context: White lesions in the oral cavity may be benign, pre-malignant or malignant. There are no signs and symptoms which can reliably predict whether a leukoplakia will undergo malignant change or not. Many systemic conditions appear initially in the oral cavity and prompt diagnosis and management can help in minimizing disease progression and organ destruction. Aim : The aim of the paper was to study the clinical and histopathological patterns of white lesions in the oral cavity presented at the study setting and to study the factors associated with the histopathological patterns of the lesions. Settings and Design: A hospital based cross-sectional study of patients with white lesions in the oral cavity attending the Department of Dermatology and Venereology, Medical College, Thiruvananthapuram was done. Materials and Methods: After taking a detailed history, microscopic examination of Potassium hydroxide smear and an oral biopsy with histopathologial examination was done. Results : Out of the 50 patients in the study, clinically the diagnoses made were Lichen planus (32 patients; 64%), Frictional Keratosis (4;8%), Dysplasia (2;4%), Oral Hairy Leukoplakia (1;2%), Pemphigus Vulgaris (2;4%), Cutaneous Lupus Erythematosus (1;2%), Oral Submucous fibrosis (3;6%) and Oral Candidiasis alone (5;10%). Out of the 45 patients who had undergone biopsy, 25 (55.6%) had Lichen planus, 9 (20%) had Frictional Keratosis and mild Dysplasia was found in 4 (8.9%) patients. Conclusion : The measure of agreement between the clinical and pathological diagnosis was only 32%. Older age, difficulty in opening the mouth, consumption of non-smoked tobacco, site of the lesion (gingival, floor of mouth or lingual vestibule) and presence of tenderness on the lesion were significantly associated with Dysplasia.